Appopriate pipe materials for earth-air-pipe heat exchanger (EAPHE) system for temperature reduction via computer simulation in hot-humid climates - Aminuddin bin Mohd Noor (Kulliyyah of Architectural and Environmental Design, International Islamic University Malaysia, 2015)
The implementation of earth-air pipe heat exchanger (EAPHE) system as a passive cooling technology for both residential and commercial buildings in the hot and humid climate of Malaysia is relatively new. To date this technology has not been implemented in Malaysia, although it is proven in many studies particularly in drier climates, that it has the potential to reduce energy consumption for passive cooling system for the country. Thinner on the ground are the potentials of the appropriate pipe materials for the EAPHE system. The objectives of the research are to study the potential of temperature reduction between ambient temperature at pipe inlet and at outlet utilizing the EAPHE system and to find the most appropriate pipe material for the EAPHE system. Finally the research intends to find the most appropriate pipe materials that will predict the optimum air temperature reduction through parametric studies for achieving thermal comfort. The study utilizes the EnergyPlus simulation program to investigate the performances of three pipe materials system: single pipe material, hybrid pipes and insulated hybrid pipes system. Through an exhaustive enumeration process, the study found that the insulated hybrid pipes with water system (Polyethylene + Water + Polyethylene) reduces the air at the outlet with a 6.233°C difference than at the inlet indicating promising cooling and energy savings potentials.